واقع صلابة وسلامة الجهاز المصرفي الجزائري في ظل اتفاقية بازل Iii - أولاد زاوي عبد الرحمان; عباسي طلال (My University, 2019)
هدفت الدراسة إلى تبيان ضرورة قياس الصلابة المالية للبنوك في ظل الأزمات المالية، وكذا إبراز دور اتفاقية بازل III في تعزيز صلابة الجهاز المصرفي بعد الأزمة المالية العالمية لسنة 2008. وباستخدام مختلف الإحصائيات والجداول توصلت الدراسة لنتائج اهمها قيام البنك المركزي باستحداث أنظمة وقوانين جديدة لتعزيز صلابة البنوك وكذا محاولة مسايرة تطبيق القواعد الاحترازية لبازل 3. The study aimed to show the need to measure the financial solidity of banks in light of financial crises, as well as to highlight the role of Basel III in strengthening the solidity of the banking system after the global financial crisis of 2008. Using the various statistics and tables, the study concluded the results of the most important of which the Central Bank introduced new regulations and laws to strengthen the hardness of banks as well as trying to follow the application of Prudential rules for Basel III